Hydrated eutectic electrolytes for high-performance Mg-ion batteries - Zhu, Yunpei; Guo, Xianrong; Lei, Yongjiu; Wang, Wenxi; Emwas, Abdul-Hamid; Yuan, Youyou; He, Yao; Alshareef, Husam N (Energy & environmental science, 2022)
Aqueous Mg-ion batteries are a promising electrochemical energy storage technology. However, Mg 2+ ions interact strongly with electrolyte molecules and electrode materials, resulting in insufficient ionic conductivity and solid-state diffusion, and consequently limited cycling stability and rate capability. Herein, we design an aqueous Mg-ion battery chemistry involving a hydrated eutectic electrolyte, an organic molecule anode, and a copper hexacyanoferrate (CuHCF) cathode. This hydrated eutectic electrolyte features a three-dimensional percolating hydrogen bond network formed by water molecules, which facilitates fast Mg 2+ transport in the electrolyte. Moreover, the suppression of water activity in the hydrated eutectic electrolyte can efficiently improve the cycling performance of the organic molecule anode by prohibiting the dissolution issue. After coupling with the open-framework CuHCF cathode, the resultant full battery delivers a wide operating voltage of 2.2 V, an energy density of 52.2 W h kg −1 , and a decent low-temperature electrochemical performance. The electrolyte and electrode chemistries proposed in this work show an alternative way to develop low-cost, safe, and high-performance Mg battery technologies. A hydrated eutectic electrolyte with 3D percolating hydrogen bond network is designed for high-performance aqueous Mg-ion batteries.